Molecular Diversity Analysis and Genetic Mapping of Pod Shatter Resistance Loci in Brassica carinata L. - Raman, Rosy; Qiu, Yu; Coombes, Neil; Song, Jie; Kilian, Andrzej; Raman, Harsh (Frontiers in Plant Science, 2017)
Seed lost due to easy pod dehiscence at maturity (pod shatter) is a major problem in several members of Brassicaceae family. We investigated the level of pod shatter tolerance in Ethiopian mustard (Brassica carinata) and identified quantitative trait loci (QTL) for targeted introgression of this trait in Ethiopian mustard and its close relatives of the genus Brassica. A set of 83 accessions of B. carinata, collected from the Australian Grains Genebank, was evaluated for pod shatter resistance based on pod rupture energy (RE). In comparison to B. napus (RE = 2.16 mJ), B. carinata accessions had higher RE values (2.53 to 20.82 mJ). A genetic linkage map of a F2 population from two contrasting B. carinata selections, BC73526 (shatter resistant with high RE) and BC73524 (shatter prone with low RE) comprising 300 individuals, was constructed using a set of 6,464 high quality DArTseq markers and subsequently used for QTL analysis. Genetic analysis of the F2 and F2:3 derived lines revealed five statistically significant QTL (LOD ≥3) that are linked with pod shatter tolerance on chromosomes B1, B3, B8 and C5. Herein, we report for the first time, identification of genetic loci associated with pod shatter resistance in B. carinata. These characterized accessions would be useful in Brassica breeding programs for introgression of pod shatter resistance alleles in to elite breeding lines. Molecular markers would assist marker-assisted selection for tracing the introgression of resistant alleles. Our results suggest that the value of the germplasm collections can be harnessed through genetic and genomics tools.